Protótipo: guia de apoio estudantil da UFRN - Santos, Ana Rita Rodrigues (2023)
This product is the result of research by Ana Rita Rodrigues dos Santos, linked to the Postgraduate Program in Special Education at the Federal University of Rio Grande do Norte (PPGEEsp/UFRN). Its objective was to design a multiformat guide, specially outlined according to techniques and procedures of communicational accessibility contributing to the dissemination of information about student support services offered at UFRN. The systematized knowledge contributed to the basis of this research, connecting scientific literature, decision-making and practice, ratified by empirical data collected during the guide development. To elaborate the content and propose the guide, design methods and tools were used, organized in macro and micro project phases, considering the scientific evidence found in the Scope Review Research that reinforce the state of the art of the study in question. The product, designed with the Inclusive Design approach, meets the requirements identified in the research, considering the diversity and specific needs of users. In this proposition and with the support of a multiprofessional team, efforts converged to design the “UFRN Student Support Guide”, a multiformat communication product, as a viable alternative to reduce and/or transpose noise in the communication process between UFRN and its university community. The guide presents itself as an effective option to provide information about student support services offered by various institutional units at UFRN and allows gathering information in a single place, in different formats and versions, facilitating quick access to information. Furthermore, it serves as a frequent consultation tool for the university community and encourages the availability, access and dissemination of information in an accessible way